ئافرهت و تهكسی تێڕوانینی ئافرهتان بهرامبهر شۆفێری تهكسی و ڕهفتاری شۆفێران - Murad Hakeem Mohammed; Aveen Abdulrahman Nooraldeen (QALAAI ZANIST JOURNAL, 2019)
The main goals of the research that the problem or the event to be clear and to obtain more idea about reasons, reality and effective of this event while this research tried describe the event scientifically and analyzing with the social sides, another goals of this study that to reduce some points that makes problem in front woman’s as using taxi there for, gives more importance to using common transportation by woman’s in their daily life so as to be safety by healthy and avoid of woman’s violence that’s another side of researchers goal , fur there more, recommend that the researchers do not stop….. Working continuously to do there feasible study on a relation woman’s issue